Effectiveness of Training on Using Loose Parts in Increasing Creativity and Innovation of Early Childhood Education Teachers - Chatarina Anggraini; Ajat; Widya Fitraini Bakir; Nuraini; Nurhayati; Ni'matus Sa'adah (International Conferences on Early Childhood Education Proceedings, 2024)
Early childhood education teachers are professionals who are required to have certain competencies and skills, especially those related to the ability to develop creative learning in early childhood education units. Facts in the field show that there are still many PAUD teachers who have low creativity, which has an impact on the continuity of learning activities, and even has an impact on the accreditation assessment of early childhood education units. Through research aimed at proving the effectiveness of training in the use of Loose Part media in increasing the creativity of early childhood education teachers, an experimental research method was designed involving one experimental group and one control group. The research subjects were Early Childhood Education (PAUD) teachers in Cluster 3, Pondok Aren District, South Tangerang City - Banten has a total of 25 people.The results of this research indicate that training in the use of Loose Part media is effective in increasing teacher creativity so that the research hypothesis is accepted (p < 0.01).